High Power SESAM Mode-Locked Laser Based on Yb3+:YAlO3 Bulk Crystal - A. Rudenkov; V. Kisel; A. Yasukevich; K. Hovhannesyan; A. Petrosyan; N. Kuleshov (Приборы и методы измерений)
Yttrium aluminium perovskite YAlO3 (YAP) crystal, doped with rare-earth ions, has been extensively studied as a diode-pumped laser host material. The wide interest to rare-earth ions doped YAP crystals is explained by its good thermal and mechanical properties, high natural birefringence, widely used Czochralski  growth method. The aim of this work was to study the Yb3+:YAlO3  crystal as an active medium for high  power mode-locked laser.Yb3+-doped perovskite-like aluminate crystals have unique spectroscopic and thermooptical properties that allowed using these crystals as an active medium of high power continuous wave (CW) and modelocked (ML) bulk lasers with diode pumping.growth method. The aim of this work was to study the Yb3+:YAlO3  crystal as an active medium for high  power mode-locked laser.In our work spectroscopic properties of Yb:YAP crystal and laser characteristics in CW and ML regimes are investigated. Maximum output power of 4 W with optical-to-optical efficiency of 16.3 % and 140 fs pulse duration have been obtained for Yb:YAP E //c-polarization with 10 % output coupler transmittance. Tunability range as wide as 67 nm confirms high promise of using Yb:YAP crystal for lasers working in wide spectral range.